Data comparing the plasma levels of procollagen C-proteinase enhancer 1 (PCPE-1) in healthy individuals and liver fibrosis patients - Hassoun, Eyal (Data Brief, 2017)
This article provides a protocol for determination of human procollagen C-proteinase enhancer 1 (PCPE-1) concentrations by ELISA. The inter-assay and intra-assay coefficients of variability are given and so are the average plasma concentrations of PCPE-1 in healthy (control) individuals and liver fibrosis patients.